On Controllability of Solution for Nonlinear Neutral Fuzzy Integro-Differential Equations (Journal of Nonlinear Modeling and Analysis, 2024)
This paper delves into an examination of the existence, uniquenessand controllability results concerning impulsive functional fuzzy nonlinear neutral integro-differential equations with non-local conditions. Additionally, weexplore the fuzzy solution within the context of normal, convex, upper semi-continuous and compactly supported interval fuzzy numbers. Our findings arederived through the application of the Banach fixed point theorem. Also, weillustrate the result with an example.
Keywords: Nonlinear neutral integro-differential equations; controllability; fuzzy solution; impulsive functional; nonlocal condition; fixed point.